Assessment of preferences and frequency of milk and selected dairy products consumption by mothers and their children aged 1 to 3 years - Aleksandra Kołota-Burdzy; Edyta Krawczuk; Anna Harton (Roczniki Panstwowego Zakladu Higieny)
Background Early childhood is a time of developing eating habits and taste preferences, which is most influenced by the family environment. Milk and dairy products play an important role in the diet of post-infant children, as they provide many nutrients that condition the proper growth and development of the young body.